2022
DOI: 10.20517/jeea.2022.13
|View full text |Cite
|
Sign up to set email alerts
|

https://www.oaepublish.com/jeea/article/view/5143

Abstract: The occurrence and risks of polychlorinated biphenyls (PCBs) in water, sediment, and fish from the Wupa River, Nigeria, were assessed in this study. Water, sediment, and fish were collected from five locations in the Wupa River in November 2019. After extraction with dichloromethane, hexane, and acetone, the PCBs were determined using gas chromatography equipped with a quadrupole mass spectrometer. The hazard index and total cancer risk models were used for risk evaluation of the detected PCBs. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, the graphic showed that ER1 had a higher concentration of PCBs than ER2 and ER3, with PCB66 predominating ER1 (Figure 6). Accidental leaks and spills, releases from contaminated soil in landfills and hazardous waste sites, deposition of vehicle emissions near roadway soil, and land application of PCB-containing sewage sludge are all possible sources of PCB release to soil [4,24]. Uncontrolled hazardous waste sites, the burning of wastes containing PCBs, the usage of obsolete electrical equipment and can all cause high PCBs to be released into the atmosphere [24,25].…”
Section: Cumulative Of Pcbs In the Nine Sediment Sitesmentioning
confidence: 99%
“…Additionally, the graphic showed that ER1 had a higher concentration of PCBs than ER2 and ER3, with PCB66 predominating ER1 (Figure 6). Accidental leaks and spills, releases from contaminated soil in landfills and hazardous waste sites, deposition of vehicle emissions near roadway soil, and land application of PCB-containing sewage sludge are all possible sources of PCB release to soil [4,24]. Uncontrolled hazardous waste sites, the burning of wastes containing PCBs, the usage of obsolete electrical equipment and can all cause high PCBs to be released into the atmosphere [24,25].…”
Section: Cumulative Of Pcbs In the Nine Sediment Sitesmentioning
confidence: 99%